2016
DOI: 10.1109/jpets.2016.2559507
|View full text |Cite
|
Sign up to set email alerts
|

A Distinctive Load Feature Extraction Based on Fryze's Time-domain Power Theory

Abstract: The performance of a non-intrusive load monitoring (NILM) system heavily depends on the uniqueness of the preferred load signature (LS) extracted from each appliance. Some electrical characteristics such as instantaneous current waveform (CW), instantaneous power waveform (IPW), current harmonic (CH) and voltage-current (V-I) trajectory have been proposed as appliance features in the literature. However, in some situations, these LSs cannot effectively distinguish different loads apart. In this paper, a time-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Nevertheless, several highly resistive loads may not be detected by this approach due to the low level of the current harmonics. The applications of V-I trajectory in NILM are discussed in [9,10]. In this scheme, the instantaneous voltage and current are respectively measured and normalized based on their peaks.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, several highly resistive loads may not be detected by this approach due to the low level of the current harmonics. The applications of V-I trajectory in NILM are discussed in [9,10]. In this scheme, the instantaneous voltage and current are respectively measured and normalized based on their peaks.…”
Section: Introductionmentioning
confidence: 99%
“…To detect the appliance ID using SMID-AO, we used a V-I trajectories curve and Fryze's Power Theory, explained further by Teshome et al, (2016) and implemented in MatLAB, as shown in Figure 5b, where the V-I trajectories are compared with a ready data set of appliance waveforms using the correlation coefficient of waveform method. Figures 5a and 5c show MatLAB Simulink simulation data inserted using an excel spreadsheet of voltage and iron appliance currents.…”
Section: Smid-oa Distinctive Load Signature Hardware Resultsmentioning
confidence: 99%
“…Using power theory concepts, Teshome et al [44] proposed a NILM with components of active, reactive, apparent power, and nonactive currents. Nguyen et al [45] created a NILM method based on active, reactive and apparent power and used a decision tree (DT) to disaggregate five loads, achieving more than 98.8% accuracy.…”
Section: Nilm State-of-the-art Reviewmentioning
confidence: 99%
“…To summarize, there are many other studies regarding NILM with different methodologies, feature extraction, different appliances in the validation and different load disaggregation algorithms. Nevertheless, in Teshome et al [44], the authors indicate the importance of modern power theories and the lack of these elegant circuit analyses to improve the NILM systems. One of these elegant power theories pointed out in Teshome et al [44] was the CPT.…”
Section: Nilm State-of-the-art Reviewmentioning
confidence: 99%